Online Education About Providing Nutrition in Immune System For Millenials During Covid-19 Pandemic - Nur Ariska Nugrahani; Dhiya Nada Putri; Devi Wulandari (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
During the Covid-19 pandemic in Indonesia, it has taken the soul and the body of the population in Indonesia, so to trigger herd immunity and optimal public health requires macro-nutrients and micro-nutrients. Optimal macro-nutrients and micro-nutrients can trigger the body's defense system to protect the body from viral, bacterial, and fungal infections. This educational activity aims to increase knowledge about macro-nutrients and micro-nutrients. The methods used include creative lectures with video, discussions with participants, and participants filling out questionnaires through the zoom meeting application. The level of knowledge of participants on the types of immune systems has a sufficient category of 64.5%, the level of knowledge of participants on the dose of vitamin consumption has a sufficient category of 67.7%, the level of knowledge of participants on habits that can damage the immune system has a good category of 80.6%, and the level of knowledge of participants about habits that can damage the immune system has a good category of 87.7% and the level of knowledge of types of food as a natural immune system